Skin Findings in a Patient with Sjogren's Syndrome. (8th September 2016) - Boddu, Prajwal; Mohammed, Abdul S.; Khandelwal, Sonali
Abstract : Hypergammaglobulinemic purpura (HGP) is a syndrome constellating recurrent purpura, hypergammaglobulinemia, positive rheumatoid factor (RF), anti-Ro/La antibodies, and elevated erythrocyte sedimentation rate (ESR). We present a case of a 29-year-old female who was diagnosed with Sjogren's syndrome four years prior to presenting with rash on her lower extremities for a period of 6 months. Skin biopsy at the initial visit was consistent with leukocytoclastic vasculitis and was initiated on treatment for it. Her rash evolved into 2–5 mm scattered purpurae while she was on the treatment and a repeat biopsy showed extravasation of RBCs, a sparse mononuclear infiltrate with deposition of plasma cells, and no evidence of leukocytoclastic vasculitis, thus showing a transition from neutrophilic to mononuclear inflammatory vascular disease which is a rare occurrence. Hypergammaglobulinemic purpura sometimes turns out to be a challenging disease to manage and requires an integrated effort from the primary care doctors, rheumatologist, and dermatologist.